Ocorrência de Clostridium botulinum tipos C e D em criatórios de bovinos no município de Cocalinho, Vale do Araguaia, Mato Grosso - Souza, Aires Manoel de; Dias Filho, Francisco de Carvalho; Dutra, Iveraldo dos Santos [UNESP]; Marques, Dercindo Francisco; Silva, Sebastiana Heloísa da; Souza, José Ailton de; Santos, Plínio Mathias dos; Godoi, Walisson pereira; Gomes, Rodrigo Otávio de Melo (My University, 2011)
In order to assess the occurrence and distribution of spores and toxins of Clostridium botulinum types C and D in three farms in Cocalinho, at the Araguaia River valley, State of Mato Grosso, Brazil, we analyzed sediment samples from 40 water holes, soil and cattle feces, collected around water holes. Sediments were analyzed by direct method, whilst feces, soil and also sediment samples were individually analyzed by indirect method. The detection of spores and botulinum toxins in the filtered material was performed by bioassay in Swiss Webster mice strain, as well as the serum-neutralization of the positive materials for typing. Samples of cattle feces showed the largest positive rate for C. botulinum, with 25/40 (62.5%), followed by soil, 12/40 (30%), and by sediment, 13/40 (32.5%). From the 40 cattle feces samples, 25 (62.00%) were positive for Clostridium botulinum; six samples were identified as type C, other six as type D, and 13 samples were classified as CD complex. From the equal number (40) of soil samples, 12 (30%) were positive for C. botulinum; two samples were identified as type C, other three as type D, and seven samples were classified as CD complex. Regarding the 40 sediment samples, 13 (32.5%) were positive for C. botulinum; two samples were identified as type C, other three as type D, and eight samples were classified as CD complex. No botulism toxin was detected by indirect method.
Occurrence of types c and d of clostridium botulinum in cattle in the city of Cocalinho, Mato Grosso, Brazil
Keywords: Serum-neutralization; Spores; Toxins; Faeces; Sediment; Soroneutralização; Esporos; Toxinas; Fezes; Sedimento